Construction of functional biliary epithelial branched networks with predefined geometry using digital light stereolithography. (December 2021) - Mazari-Arrighi, Elsa; Ayollo, Dmitry; Farhat, Wissam; Marret, Auriane; Gontran, Emilie; Dupuis-Williams, Pascale; Larghero, Jerome; Chatelain, Francois; Fuchs, Alexandra
Abstract: Cholangiocytes, biliary epithelial cells, are known to spontaneously self-organize into spherical cysts with a central lumen. In this work, we explore a promising biocompatible stereolithographic approach to encapsulate cholangiocytes into geometrically controlled 3D hydrogel structures to guide them towards the formation of branched tubular networks. We demonstrate that within the appropriate mix of hydrogels, normal rat cholangiocytes can proliferate, migrate, and organize into branched tubular structures with walls consisting of a cell monolayer, transport fluorescent dyes into the luminal space, and show markers of epithelial maturation such as primary cilia and continuous tight junctions. The resulting structures have dimensions typically found in the intralobular and intrahepatic biliary tree and are stable for weeks, without any requirement of bulk supporting material, thereby offering total access to the external side of these biliary epithelial constructs. Graphical abstract: Image 1 Highlights: Branched bile ducts of controlled geometry spanning hundreds of microns were fabricated by DLP stereolithography. Bile ducts of intrahepatic dimensions had a central closed lumen and were stable for at least 21 days in culture. Bile ducts showed active transport functions and cholangiocytes formed primary cilia facing the luminal space. This is the first  in vitro  model of the intrahepatic biliary tree obtained by high-resolution 3D printing